The Ayala gazette : an AC Knowledge Management publication (Makati City : Ayala Corporation - Knowledge Management, 2018)
"...the Ayala Gazette creates greater awareness and appreciation for Ayala's legacy to business and its contributions to industry, social, and national development."
Keywords: Ayala Corporation; Ayala Group of Companies